Career success of expatriates: the impacts of career capital, expatriate type, career type and career stage - Mello, Rodrigo; Suutari, Vesa; Dickmann, Michael (Emerald, 2023)
Purpose This paper investigates whether career capital (CC) development abroad, expatriate type, career type, and career stage affect expatriates’ career success in terms of perceived marketability and the number of promotions. Design/methodology/approach The study presents findings from a 2020 follow-up study among 327 expatriates, including assigned expatriates (n=117) and self-initiated expatriates (n=220), who worked abroad in 2015 and 2016. Among that group, 186 had continued their international career, while 141 had repatriated. Structural equation modeling with robust maximum likelihood estimation was used to test this study’s hypotheses. MPlus 8.6 software supported the analysis. Findings The study outlines that CC developed abroad positively impacts perceived marketability and the number of promotions. Second, repatriates reported a greater degree of perceived marketability than those continuing an international career. Career type did not predict the number of promotions. The expatriate type did not influence any of the career success measures. Finally, expatriates in their late career stage did not achieve a similar level of career success as those in other career stages. Research limitations/implications All the expatriates were university-educated Finnish engineers and business professionals, and the career benefits of expatriation could differ for different sample groups. The study calls for more context-sensitive global careers research. The findings have positive implications for self-guided career actors considering working abroad. Organizations could focus more of their global talent attraction, management, and career efforts on self-initiated expatriates.
Keywords: Career Success; Perceived Marketability; High-Density Work; Assigned Expatriates; Self-initiated Expatriates; Career Capital